Hypertension self-care practice and associated factors among patients in public health facilities of Dessie town, Ethiopia - Sewunet Ademe; Fekadu Aga; Debela Gela (BMC, 2019)
Abstract Background Hypertension self-care practice is essential for blood pressure control and reduction of hypertension complications. Nevertheless, we know little concerning hypertension self-care practice in Ethiopia. The purpose of this study was to assess hypertension self-care practice and associated factors among patients in public health facilities in Dessie town, Ethiopia. Methods In this cross-sectional study, 309 hypertensive patients (mean age 58.8 years, 53.4% women) completed the interviewer-administered questionnaire in Amharic language. Descriptive and logistic regression analyses were conducted using SPSS version 22. Result The mean score for hypertension self-care was 37.7 ± 8.2 and 51% scored below the mean. Divorced participants (AOR = 0.115, 95% CI = 0.026, 0.508, p-value < 0.01) and those who lack source of information (AOR = 0.084, 95% CI = 0.022, 0.322, p-value < 0.01) were less likely to have good self-care practice. But, participants who had convenient place for exercise (AOR = 2.968, 95% CI = 1.826, 4.825, p-value < 0.01), who had good social support (AOR = 2.204, 95% CI = 1.272, 3.821, p-value < 0.01), who had traditional clergy-based teaching (AOR = 2.209, 95% CI = 1.064, 4.584, p-value < 0.05), and who had good self-care agency (AOR = 1.222, 2.956, p-value < 0.05) were more likely to have good self-care practice. Conclusion Most of the study participants reported poor self-care practices. Factors associated with hypertension self-care practice are marital status, education, source of self-care information, place for exercise, social support, and self-care agency. Targeted interventions are needed to improve hypertension self-care practice.